How to read effectively and efficiently - Ahuja, Pramilla (India)
The book is effective and efficient rading is an art by itself. It involves the accurate recognition of words and the fusion of specific meaning represented as a chain of related ideas.
Keywords: Reading; Reading Abilities; Speed Reading